Translating the WHO 25×25 goals into a UK context: the PROMISE modelling study - Cobiac, L; Scarborough, P (BMJ Publishing Grou, 2017)
OBJECTIVE: Model the impact of targets for obesity, diabetes, raised blood pressure, tobacco use, salt intake, physical inactivity and harmful alcohol use, as outlined in the Global Non-Communicable Disease Action Plan 2013-2020, on mortality and morbidity in the UK population. DESIGN: Dynamic population modelling study. SETTING: UK population. PARTICIPANTS: Not available. MAIN OUTCOME MEASURES: Mortality and morbidity (years lived with disability) from non-communicable diseases (NCDs) that are averted or delayed. Probability of achieving a 25% reduction in premature mortality from NCDs by 2025 (current WHO target) and a 33% reduction by 2030 (proposed target). RESULTS: The largest improvements in mortality would be achieved by meeting the obesity target and the largest improvements in morbidity would be achieved by meeting the diabetes target. The UK could achieve the 2025 and 2030 targets for reducing premature mortality with only a little additional preventive effort compared with current practice. Achieving all 7 risk targets could avert a total of 300 000 deaths (95% uncertainty interval 250 000 to 350 000) and 1.3 million years lived with disability (1.2-1.4 million) from NCDs by 2025, with the majority of health gains due to reduced mortality and morbidity from heart disease and stroke, and reduced morbidity from diabetes. Potential reductions in morbidity from depression and in morbidity and mortality from dementia at older ages are also substantial. CONCLUSIONS: The global premature mortality targets are a potentially achievable goal for countries such as the UK that can capitalise on many decades of effort in prevention and treatment. High morbidity diseases and diseases in later life are not addressed in the Global NCD Action Plan and targets, but must also be considered a priority for prevention in the UK where the population is ageing and the costs of health and social care are rising.